2015
DOI: 10.2319/092814-696.1
|View full text |Cite
|
Sign up to set email alerts
|

Dental and skeletal changes in mild to moderate Class II malocclusions treated by either a Twin-block or Xbow appliance followed by full fixed orthodontic treatment

Abstract: Objective: To compare the short-term skeletal and dental effects of two-phase orthodontic treatment including either a Twin-block or an XBow appliance. Materials and Methods: This was a retrospective clinical trial of 50 consecutive Class II cases treated in a private practice with either a Twin-block (25) or XBow (25) appliance followed by full fixed orthodontic treatment. To factor out growth, an untreated Class II control group (25) was considered.Results: A MANOVA of treatment/observation changes followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The lack of mandibular skeletal growth in the X-Bow appliance group might have been due to the short duration of active treatment or the fact that the X-Bow appliance is a non-protrusive Class II corrector. 25 Paired t-test, comparison of pre-and post-treatment measurements within groups, the significance level was p < 0.05. *Statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of mandibular skeletal growth in the X-Bow appliance group might have been due to the short duration of active treatment or the fact that the X-Bow appliance is a non-protrusive Class II corrector. 25 Paired t-test, comparison of pre-and post-treatment measurements within groups, the significance level was p < 0.05. *Statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared fixed functional appliances with removable functional appliances with regard to dentoskeletal effects. Ehsani et al 25 compared the effects of the Twin-block and X-Bow appliances and found a greater increase in mandibular incisor inclination using the X-Bow appliance and corpus length increase in the Twin-block group. Similar to the findings of Ehsani et al, 25 the present study found a larger sagittal increase in the mandible in the Frankel and Trainer groups compared with the X-Bow group, while the X-Bow group experienced greater mandibular incisor proclination.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The jaw epidemic is therefore a recent phenomenon and temporal and geographic correlation strongly suggests that it can be traced to changes in environmental factors due to agriculture and industrialization, but exactly what those factors are and how they operate remain uncertain. Indeed, environmental influences on skeletal growth are largely ignored by the orthodontic profession, which often accepts jaw skeletal development as genetic in nature, although the teeth themselves are recognized as subject to environmental influences (Proffit 1978 , Tulloch et al 1998 , 2004 , Dolce et al 2007 , Siara-Olds et al 2010 , Ehsani et al 2015 ).…”
Section: Origins: Evolutionary and Environmental Causes Of The Epidemmentioning
confidence: 99%
“…[ 2 ] The Class II division 1 patients with deficient mandible should be diagnosed and treated during the pubertal period. [ 3 ] The assessment of growth is important to identify abnormal growth from normal growth which can be assessed by pubertal markers and skeletal maturity indicators. [ 4 ] Various appliances were indicated for this treatment but failed to reach the expectations of the orthodontists.…”
Section: Introductionmentioning
confidence: 99%